Officers of the Rocky Mountain Coal Mining Institute 1925 (Rocky Mountain Coal Mining Institute, 1925)
[JOHN B. MARKS President Boston Bldg., Denver, Colo. BENEDICT SHUBART Secretary-Treasurer 521 Boston Bldg., Denver, Colo. H. H. BUBB Vice-President for Colorado Cokedale, Colo. W. J. REID Vice-President for Utah Wattis, Utah WM. MOORHEAD Vice-President for New Mexico Dawson, New Mexico GOMER REESE Vice-President for Wyoming Frontier, Wyoming EXECUTIVE BOARD COLORADO: E. H. McCLEARY Alamo SAMUEL TESCHER Denver UTAH: DAVE BROWN Storrs JOHN JENNINGS Hiawatha NEW MEXICO: JAS. McDOUGALL Van Houten GEO. MIKSCH Gallup WYOMING T. H. BUTLER Hanna L. A. NORMAN Sheridan]